Production Potential of Sweet Potato Based Intercropping System in Sylhet Region - Nazrul, MI (Bangladesh Journal of Agricultural Research, 2023)
A field experiment was conducted during two consecutive years 2017-18 and 2018-19 at farming system research and development (FSRD) site, under South Surma Upazilla of Sylhet in Bangladesh to find out the suitable crop combination for increasing total productivity, return and maximizing land utilization through intercropping. Five treatments viz. T1: Sweet potato + red amaranth, T2: Sweet potato + leaf amaranth, T3: Sweet potato + mustard green, T4: Sweet potato + mustard and T5: Sweet potato sole (100% sweet potato) were considered in the experiment. Results showed none of the intercrop-combination influenced the root yield of sweet potato. Tuberous root yield of sweet potato in 100% sweet potato + 100% mustard green combination was at per sweet potato sole cultivation. Sweet potato yield did not reduce significantly due to intercropping. The highest sweet potato equivalent yield (41.75 t ha-1), land equivalent ratio (1.37), gross return (Tk. 625950 ha-1), gross margin (Tk. 495500 ha-1) and benefit cost ratio (4.80) were recorded from sweet potato 100% + mustard green 100% combination. On the contrary, sweet potato sole gave the lowest sweet potato equivalent yield (30.60 t ha-1), gross margin (Tk.330300 ha-1) and benefit cost ratio (3.57). The results revealed that sweet potato 100% + mustard green 100% intercropped combination might be suitable for higher productivity and economic return. Bangladesh J. Agril. Res. 46(2): 123-131, June 2021